The Missing Piece: Concentration Dependence of Donor‐Acceptor Stenhouse Adduct (DASA) Reactivity. Issue 8 (5th May 2021) - Alves, Jessica; Wiedbrauk, Sandra; Barner‐Kowollik, Christopher; Blinco, James P.
Abstract: Donor‐Acceptor Stenhouse Adducts (DASAs) are molecular photoswitches that reversibly isomerize from a linear to a cyclized form upon visible light irradiation. In the cyclized form, these molecules selectively react with a thiol in a thiol‐Michael addition. Driven by the complexity of the switching mechanism and chemical properties of DASAs, the effect of concentration (ranging from 1 to 5 mM DASA) on the thiol‐Michael addition was investigated. We find that the rate limiting step in the reaction is the photochemically induced DASA isomerization, as higher concentrations of thiol do not alter the rate at which the thiol‐Michael adduct (TMA) is formed. Moreover, the kinetics of the product formation were found to be more significantly affected by irradiation at higher concentrations. In two distinct scenarios, where either the concentration or the molar equivalence of the reaction partner was kept constant, the TMA was found to be more efficiently formed under irradiation at higher concentrations. These findings indicate that the DASA reactivity towards thiol‐Michael reactions appear to be equilibrium‐driven at lower concentrations and light‐driven at higher concentrations. Abstract : The puzzle is nearly complete : The effect of the donor‐acceptor Stenhouse adduct (DASA) concentration on its reactivity with an activated thiol is investigated. A thiol‐Michael addition on a DASA occurs only on its cyclized form, commonly formed by light irradiation. We find that the reaction occurs over a range of concentrations, despite the complexity of the DASA switching. Additionally, the equilibrium between the two DASA isomers dominates the light effect at low DASA concentrations.